Proposing a new method for calculating DC sources in an extended multilevel converter - Afzal Keivanlou Shahrestanaki; Rahim Ildarabadi; Mahmoud Zadehbagheri; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
In this paper, we propose a method for calculating the DC source amplitude in an extended multilevel inverter (MLI) structure so that the maximum number of levels and the output voltage waveform are as close as possible to the sinusoidal wave with minimum total harmonic distortion (THD). For the developed structure, three algorithms are suggested to determine the amounts of DC voltage resources. The first important point about choosing the right amounts for the DC resources is that the number of levels should be as large as possible, and the second important point is that the intervals between the levels should be the same throughout the waveform. By observing these two points, the output voltage waveform can be as near as possible to the sinusoidal wave that we want. In this study, we used iteration-based methods to find suitable values for DC sources. Simulation results are offered to confirm the capability of the extended multilevel converter. After we solved the problem through calculation and analysis, a code was written in MATLAB with the aim that this time the code will tell us for what values of DC sources we will have the largest number of levels and as we expected, the output of the MATLAB code confirmed the correctness of the calculations.